PENINGKATAN KETERAMPILAN MENULIS PUISI BERBASIS KEARIFAN LOKAL BANYUWANGI MELALUI METODE COPY THE MASTER (CTM) MEDIA GAMBAR - Rima Trianingsih; Ahmad Izza Muttaqin; Riza Faishol (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
In the industrial revolution 4.0, teachers should be able to become agents of change. Teachers should be able to answer every challenge and solve problems that occur at school. Preliminary study learning issues of the 2013 curriculum on grade five SDN 1 Sumberbaru is students have less writing skills. Therefore, the research aims to improve poetry writing skills based on local wisdom Banyuwangi through Copy The Master (CTM) method with a media image in grade five students SDN 1 Sumberbaru Banyuwangi. This research is a classroom action research. The instruments used are portfolio reflections, product valuation sheets, observations and documentation. The result of this research was an increase in the results of the students poetry with a gain score of average value of cycle 1 and a 7 cycle of 15.89. The process assessment results also showed an increase of 48.15% in the category of skilled and highly skilled students. The research conclusion is that there is an increase in poetry writing skills students.